Optimal central bank design: benchmarks for the ECB - Helge Berger (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2005)
The paper discusses key elements of optimal central bank design and applies its findings to the Eurosystem. A particular focus is on the size of monetary policy committees, the degree of centralization, and the representation of relative economic size in the voting rights of regional (or sectoral) interests. Broad benchmarks for the optimal design of monetary policy committees are derived, combining relevant theoretical arguments with available empirical evidence. A new indicator compares the mismatch of relative regional economic size and voting rights in the monetary policy committees of the US Fed, the pre-1999 German Bundesbank, and the ECB over time. Based on these benchmarks, there seems to be room to improve the organization of the ECB Governing Board and current plans for reform.
Keywords: D72; E58; 330; Central bank design; federal central banks; ECB; Eurosystem; ECB reform; Zentralbank; Vorstand; Organisation; Benchmarking; Europäische Wirtschafts- und Währungsunion; EU-Staaten; USA; Deutschland